Penerapan Metode Flipped Classroom dalam Peningkatan Kemampuan Speaking - Suparlan, Suparlan; Masyudi, Masyudi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The aim of this research is to determine the improvement in speaking ability of class XI students at SMA Negeri 01 Aikmel, Kecamatan Aikmel, Kabupaten Lombok Timur using the Flipped Classroom method. Classroom action research is the type of research used in this research. The object of this research is SMA Negeri 01 Aikmel, Kecamatan Aikmel, Kabupaten Lombok Timur, Provinsi Nusa Tenggara. The use of speaking tests and observation sheets was used to collect data in this research. The data was analyzed and the data obtained in cycle II experienced an increase with a score of 83.17%, cycle I also experienced an increase with an average score of 72.87% and in pre-action an average score of 62.78% was obtained, which shows 77% of students having problems in speaking. From the results of this research, it can be concluded that the Flipped Classroom method can improve the speaking skills of class XI students at SMA Negeri 01 Aikmel, Kecamatan Aikmel, Lombok Timur.